Computerized system of planning and control of use of airspace - Лупандин, М. В.; Бескровная, И. А.; Радченко, С. И.; Устинов, П. А.; Шутов, В. Г. (Proceedings of National Aviation University (archive), 2000)
Considered is computerized system of planning air traffic. Presented is the list of computerized functions and problems, also technology of their processing on the computerized working stations